Managerial Ownership and Tax Aggressiveness with Profitability Moderation: Ex-ante Period of Fiscal Transition Due to the Pandemic - Prakoso, Damar Agung; Lasmana, Mienati Somya; Hartadinata, Okta Sindhu (E-Jurnal Akuntansi, 2025)
This study aims to examine the effect of managerial ownership on tax aggressiveness by using profitability as a moderating variable. The research population uses manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 2016-2020 period. The sample selection method used was purposive sampling and obtained 379 samples of data that met the criteria. Testing the research hypothesis using multiple regression analysis and Moderated Regression Analysis (MRA). The result show that managerial ownership had a negative effect on tax aggressiveness. It means, the higher managerial ownership in company, the lower tax aggressiveness action, while profitability is proven to be able to moderate the effect of managerial ownership on tax aggressiveness. This research provides the implication that managerial ownership can reduce agency costs thereby aligning the interests of management and shareholders and reducing the potential for tax aggressiveness. Keywords: Managerial Ownership; Profitability; Tax Aggressiveness